Evidence of subchondral bone's effects on articular cartilage damage in OVX-OA rat. (15th June 2020) - Zhao, Zhenda; Tan, Qizhao; Jiang, Ai; Sun, Shang; Liu, Zhongjun; Li, Weishi; Song, Chunli; Leng, Huijie
Highlights: First-time investigation of correlation between cartilage and subchondral bone alterations using the term of change ratio. Comprehensive characterization of cartilage including histomorphological, immunohistochemical and mechanical evaluation. Comparison between osteochondral units in femur and tibia to exclude estrogen effects on cartilage damage. Direct evidence that subchondral bone alterations can affect cartilage damage in OVX-OA. Abstract: The role of subchondral bone in cartilage damage attracts increasing interests in osteoarthritis (OA) research. Subchondral bone might play more important roles in cartilage damage for postmenopausal women due to estrogen's remarkable influence on bone metabolism. However, it still lacks direct evidence on the role of subchondral bone since estrogen can influence metabolisms of cartilage and subchondral bone at the same time. This study adopted the OVX-OA rat model. Damage scores and mechanical properties of cartilage and trabecular parameters of subchondral bone were evaluated. Change ratios of all the parameters at week 9 relative to week 3 which represented alterations after OVX were calculated. The results showed that change ratios of subchondral bone and cartilage damage in femur unit were both significantly lower than those in tibia unit. The two units were under the same estrogen level. That lower cartilage damage responded to lower subchondral bone change in femur unit provided evidence that articular cartilage damage might directly be affected by mechanical environmental changes induced by subchondral bone alteration in OVX-OA. Thus, for clinics, subchondral bone might be an new treatment target for this type of OA; for numerical simulation of articular joint, subchondral bone and cartilage shouldn't be modeled as two independent parts.